FUTURE PROOF CONSTRUCTION WITH INNOVATIVE SUSTAINABLE BUILDING MATERIALS - Emilia van Egmond (Department of Architecture, Institut Teknologi Sepuluh Nopember (ITS), 2019)
It is unquestionable that the construction performance needs to improve, despite itsimportance to the national economies. This industry is commonly characterized as one that is labour intensive, rather polluting, non-sustainable, with a low level of innovation compared to other sectors. Lessons from the past in other sectors indicate that a sequence of innovations pushed forward productivity and performance, reflecting the existence of a technology and knowledge base amongst the players in those sectors. Notwithstanding some innovative developments in the course of time, a wide spread change of performance on large scale in construction is limited. The objective of this paper is to discuss strategies to enhance the development and use of innovative sustainable building materials in construction. It draws on empirical evidence and contemporary theoretic views regarding the factors impeding or stimulating innovation. These learn that innovationsrequire strong collaboration amongst the construction players in the industry network to achieve sustainability in construction.